2016
DOI: 10.1111/1756-185x.12960
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of vitamin D replacement therapy on patients with chronic nonspecific widespread musculoskeletal pain with vitamin D deficiency

Abstract: Aim: The objective of this study is the evaluation of the effect of vitamin D replacement treatment on musculoskeletal symptoms and quality of life in patients with chronic widespread musculoskeletal pain (CWP) including fibromyalgia (FM) and vitamin D deficiency.Method: Patients with nonspecific CWP and vitamin D deficiency (25-OH D3 < 25 ng/mL) were included into the study. Replacement treatments of 50 000 IU/week oral vitamin D3 for 3 months were given to the patients. Patients were assessed pre-and post-tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 44 publications
1
46
0
2
Order By: Relevance
“…However, a higher reduction rates in the FIQ score and BDI score have been suggested as clinically significant by some authors [28]. In a recent study by Yilmaz et al [29] including patients with chronic nonspecific widespread musculoskeletal pain, it was reported that replacement of vitamin D improved the quality of life (SF-36). In another study, there were no correlations found between vitamin D and health status [30].…”
Section: Discussionmentioning
confidence: 99%
“…However, a higher reduction rates in the FIQ score and BDI score have been suggested as clinically significant by some authors [28]. In a recent study by Yilmaz et al [29] including patients with chronic nonspecific widespread musculoskeletal pain, it was reported that replacement of vitamin D improved the quality of life (SF-36). In another study, there were no correlations found between vitamin D and health status [30].…”
Section: Discussionmentioning
confidence: 99%
“…Osteomalazi kliniğinde en yaygın yakınma ise sıklıkla pelvis, kosta ve omurgaları içeren yaygın ağrıdır (11). Fiziksel tıp ve rehabilitasyon polikliniklerinde görülen hastaların önemli bir kısmının yakınması da özgül olmayan kas iskelet sistemi ağrılarıdır (24). Günümüzde kronik yaygın ağrı ve DVE arasındaki ilişkiyi araştıran klinik ve toplum çalışmalarının sonuçları çelişkilidir (16,17,24).…”
Section: Discussionunclassified
“…Fiziksel tıp ve rehabilitasyon polikliniklerinde görülen hastaların önemli bir kısmının yakınması da özgül olmayan kas iskelet sistemi ağrılarıdır (24). Günümüzde kronik yaygın ağrı ve DVE arasındaki ilişkiyi araştıran klinik ve toplum çalışmalarının sonuçları çelişkilidir (16,17,24). Yapılan bir toplum çalışmasında, kronik yaygın ağrı ile DVE arasında erkek cinsiyette herhangi bir ilişki saptanmaz iken, kadın cinsiyette ilişkinin istatistiksel olarak anlamlı düzeye ulaştığı bildirilmiştir (25 …”
Section: Discussionunclassified
“…Researchers have shown that women with 25OHD serum levels <20 ng/mL have a higher chance of developing pain (Table 2) (Hicks et al 2008, Heidari et al 2010. Several studies have indicated that vitamin D supplementation (Table 2) is effective in reducing complaints in specific or nonspecific musculoskeletal pain disorders (Schreuder et al 2012, Gendelman et al 2015, Yilmaz et al 2016, Ghai et al 2017. In a recent meta-analysis (Table 2), Wu and colleagues (Wu et al 2016) 3 months reduced pain in conditions such as myalgia, arthritis and chronic musculoskeletal pain.…”
Section: Vitamin D and Painmentioning
confidence: 99%